Learning Autodesk 3DS Max 2015 - Mennenoh, Brian (Infinite Skills, 2014)
"In this 3DS Max 2015 training course, expert author Brian Mennenoh introduces you to the tools and functions found in this 3D software from Autodesk. This course is designed for the absolute beginner, meaning no prior experience of 3DS Max is required. You will start by touring the user interface, then jump into learning how to model a cave using a reference image for the cave layout. Brian will teach you how to model a character, including forming the character body, adding hair, and adding symmetry and making adjustments. This video tutorial will cover topics such as adding materials for the walls, floor, and room, setting pivot points, and adding lighting and environmental effects. Finally, you will learn how to animate and render the scene. Once you have completed this computer based training course, you will be fully capable of using this 3DS software to create your own models and animations. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.